Low-boom low-drag solutions through the evaluation of different supersonic business jet concepts - Sun, Yicheng; Smith, Howard (Cambridge University Press, 2019)
This paper evaluates six supersonic business jet (SSBJ) concepts in a multidisciplinary design analysis optimization (MDAO) environment in terms of their aerodynamics and sonic boom intensities. The aerodynamic analysis and sonic boom prediction are investigated by a number of conceptual-level numerical approaches. The panel method PANAIR is integrated to perform automated aerodynamic analysis. The drag coefficient is corrected by the Harris wave drag formula and form factor method. For sonic boom prediction, the near-field pressure is predicted through the Whitham F-function method. The F-function is decomposed to the F-function due to volume and the F-function due to lift to investigate the separate effect on sonic boom. The propagation method for the near-field signature in a stratified windy atmosphere is the waveform parameter method. In this research, using the methods described and publically available data on the concepts, the supersonic drag elements and sonic boom signature due to volume distribution and lift distribution are analysed. Based on the analysis, low-boom and low-drag design principles are identified.
Keywords: Supersonic business jet (SSBJ); Multidisciplinary design analysis and optimization (MDAO); Sonic boom; Low-boom low-drag design